In Vivo Cross-sectional Characterization of Cerebral Alterations Induced by Intracerebroventricular Administration of Streptozotocin - Kraska, Audrey; Santin, Mathieu D.; Dorieux, Olène; Joseph-Mathurin, Nelly; Bourrin, Emmanuel; Petit, Fanny; Jan, Caroline; Chaigneau, Marion; Hantraye, Philippe; Lestage, Pierre; Dhenain, Marc (PLOS ONE, 2012)
Cerebral aging is often associated with the occurrence of neurodegenerative diseases leading to dementia. Animal models are critical to elucidate mechanisms associated to dementia and to evaluate neuroprotective drugs. Rats that received intracerebroventricular injection of streptozotocin (icv-STZ) have been reported as a model of dementia. In these animals, this drug induces oxidative stress and brain glucose metabolism impairments associated to insulin signal transduction failure. These mechanisms are reported to be involved in the pathogenesis of Alzheimer's disease and other dementia. Icv-STZ rats also display memory impairments. However, little is known about the precise location of the lesions induced by STZ administration. In this context, the present study characterized the cerebral lesions induced by two-doses of icv-STZ by using high-field magnetic resonance imaging to easily and longitudinally detect cerebral abnormalities and by using immunohistochemistry to evaluate neuronal loss and neuroinflammation (astrocytosis and microgliosis). We showed that, at high doses, icv-STZ induces severe and acute neurodegenerative lesions in the septum and corpus callosum. The lesions are associated with an inflammation process. They are less severe and more progressive at low doses. The relevance of high and low doses of icv-STZ to mimic dementia and evaluate new drugs is discussed in the final part of this article.